2019
DOI: 10.2147/cia.s218849
|View full text |Cite
|
Sign up to set email alerts
|

<p>Relationship Between Potentially Inappropriate Medications And The Risk Of Hospital Readmission And Death In Hospitalized Older Patients</p>

Abstract: ObjectiveThis study aimed to compare the prevalence of potentially inappropriate medications (PIMs) among hospitalized elderly patients using Beers and Chinese criteria and identify the correlation between PIMs and the risk of hospital readmission and death.MethodsThis study was conducted on geriatric patients aged ≥65 years at Beijing Fuxing Hospital between June 2015 and December 2017. The Beers criteria of 2015 and the Chinese criteria of 2017 were used to detect PIMs. Follow-ups were conducted for 12–36 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
6
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 27 publications
3
36
6
1
Order By: Relevance
“…Our results showed no significant difference between readmitted patients and those that were not readmitted in regard to the use of PIMs, FRIDs or three or more psychoactive drugs, which is in agreement with previous research [9,57]. Other studies [58,59], however, do show an association between the use of PIMs and an increased risk of being readmitted to hospital. In these studies the follow-up time was longer than 30 days implying that the use of PIMs may be a risk factor of readmission to hospital in the long run but not within 30 days.…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed no significant difference between readmitted patients and those that were not readmitted in regard to the use of PIMs, FRIDs or three or more psychoactive drugs, which is in agreement with previous research [9,57]. Other studies [58,59], however, do show an association between the use of PIMs and an increased risk of being readmitted to hospital. In these studies the follow-up time was longer than 30 days implying that the use of PIMs may be a risk factor of readmission to hospital in the long run but not within 30 days.…”
Section: Discussionsupporting
confidence: 92%
“…In the first place, the HRPOMs referred to non-steroidal anti-inflammatory drugs (NSAIDs, aspirin≤100mg/day excluded) that were used by 257 participants (31.7%). The utilization rate of NSAIDs in our study was much higher than what was reported in previous literature regarding geriatric medication 26,30,31 mainly due to their foundational role in postsurgical analgesic, anti-inflammatory, anti-stress 32 and anti-fever. Whereas the short-term use of postsurgical NSAIDs is associated with increased risk of bleeding 33 and acute kidney injury 34 especially in the older population and/or patients with related underlying medical conditions.…”
Section: Discussioncontrasting
confidence: 75%
“…39 In comparison with the PIMs based on Chinese criteria, Beers-defined PIMs engendered more substantial adverse outcomes, such as rehospitalization. 8 One additional consideration is that the Chinese criteria were revised in 2017, and it may need to be updated with new information about currently available drugs. The Beers list that was updated in 2019 demonstrated a more robust evidence of PIMs use in Chinese geriatric inpatients than the 2015 version.…”
Section: Discussionmentioning
confidence: 99%
“…5 The use of Beers-PIMs has been associated with a range of adverse events including falls, fractures, cognitive dysfunction and rehospitalization, along with increased health expenditure. [6][7][8][9][10] The prevalence of CAD-PIMs in the geriatric population ranged from 20% to 60% in the USA, Sweden and Ethiopia. [11][12][13] A study in Taiwan stated that 86.1% of older patients with both heart failure and diabetes were taking PIMs.…”
Section: Introductionmentioning
confidence: 99%